2017
DOI: 10.1089/cap.2016.0133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Psychopharmacotherapy on Body Mass Index Among Children and Adolescents with Bipolar Disorders

Abstract: The long-term use of atypical antipsychotics, both as monotherapy or in combination with other psychotropic medications in children and adolescents with bipolar disorder, was associated with a steady and cumulative increase in BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…The CEMR database has been extensively used for health outcome academic research worldwide in the fields of diabetes [ 21 - 26 ], cardiovascular research [ 27 - 31 ], obesity [ 32 - 34 ], inflammatory diseases [ 35 - 38 ], mental health [ 39 - 41 ], and other diseases [ 42 , 43 ]. To draw meaningful inferences from such studies and to generalize the results, it is essential to understand the underlying population.…”
Section: Introductionmentioning
confidence: 99%
“…The CEMR database has been extensively used for health outcome academic research worldwide in the fields of diabetes [ 21 - 26 ], cardiovascular research [ 27 - 31 ], obesity [ 32 - 34 ], inflammatory diseases [ 35 - 38 ], mental health [ 39 - 41 ], and other diseases [ 42 , 43 ]. To draw meaningful inferences from such studies and to generalize the results, it is essential to understand the underlying population.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have identified predictors of antipsychoticrelated weight gain in youths with schizophrenia spectrum disorders, and no moderators have been identified. In terms of predictors of weight gain in adults and youth, the only definitive predictor is which particular antipsychotic is prescribed, with most studies finding that atypical antipsychotics (e.g., risperidone and olanzapine) cause more weight gain than first-generation antipsychotics (e.g., molindone) and that olanzapine is particularly obesogenic (Fraguas et al 2011;Mostafavi et al 2017;Patel et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Atypical antipsychotics are a widely prescribed group of psychotropic drugs. While having distinct advantages over the conventional antipsychotics, they are associated with metabolic adverse effects such as obesity, hyperglycemia, and dyslipidemia [ 1 3 ]. Since a large number of patients on atypical antipsychotics are likely to be children and young adults, these metabolic adverse effects can lead to significant morbidity and mortality over the long term, although the link between the use of antipsychotics and mortality is not well established [ 4 7 ].…”
Section: Introductionmentioning
confidence: 99%